The Potential of Immobilized Bacteria for Pollutant Bioremediation in The Environment: Systematic Review - Harvianti, Yuniar; M. Ali Azis Hasan Rizki (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
The Environmental pollution caused by industrial waste including oil spills have become a global issue that requires effective and environmentally friendly solutions. Bioremediation used by bacteria immobilized has been develop as a promising method for pollutant degradation, because it can increase the stability and activity of microorganism under various condition in the environment. This study is a systematic review to evaluate various immobilized technique including adsorption, entrapment, adsorption-embedding, cross linking and the techniques effectiveness in hydrocarbon, crude oil, and heavy metals remediation. This review collates a vast amount of existing literature on the myriad contaminants treated using immobilized bacteria. Based on the reviewed article, the immobilization techniques such as adsorption, adsorption-embedding, entrapment and cross-linking were frequently reported to enhance degradation performance, particularly in crude oil bioremediation. The techniques consistently demonstrated high effectiveness in pollutant degradation across different environmental conditions. The environmental factors, including pH, pollutant concentration and surfactant availability have an important role in the success of bioremediation. Although, this technology enhances bacterial resilience and biodegradation efficiency, the challenges such as the hight cost of immobilization materials and limitations in extreme environment application remain a problem. The optimization techniques and immobilized materials has the potential to provide a sustainable solution for pollutant bioremediation in the environment